2006
DOI: 10.1073/pnas.0510477103
|View full text |Cite
|
Sign up to set email alerts
|

Elk-1 associates with the mitochondrial permeability transition pore complex in neurons

Abstract: Using coimmunoprecipitation and reciprocal coimmunoprecipitation from adult rat brain, we found an association between Elk-1 protein and the mitochondrial permeability transition pore complex (PTP), a structure involved in both apoptotic and necrotic cell death. Electron microscopy in adult rat brain sections confirmed this association with mitochondria. Elk-1 was also identified from purified mitochondrial fractions by using Western blotting, and Elk-1 increased its association with mitochondria following pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
53
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(60 citation statements)
references
References 33 publications
7
53
0
Order By: Relevance
“…The phosphorylation-dependent trafficking of Elk-1 to the nucleus is a major observation because, within the cytoplasm, Elk-1 is associated with the mitochondrial PTP (Permeability Transition Pore complex), an interaction that increases in the context of proapoptotic treatments (Barrett and al., 2006b). Furthermore, restricting Elk-1 transcription and translation in neurites, using a focal transfection procedure named "phototransfection", produces cell death, whereas its introduction and translation in cell bodies does not (Barrett et al, 2006a).…”
Section: Discussionmentioning
confidence: 99%
“…The phosphorylation-dependent trafficking of Elk-1 to the nucleus is a major observation because, within the cytoplasm, Elk-1 is associated with the mitochondrial PTP (Permeability Transition Pore complex), an interaction that increases in the context of proapoptotic treatments (Barrett and al., 2006b). Furthermore, restricting Elk-1 transcription and translation in neurites, using a focal transfection procedure named "phototransfection", produces cell death, whereas its introduction and translation in cell bodies does not (Barrett et al, 2006a).…”
Section: Discussionmentioning
confidence: 99%
“…Protein content of the resultant cytosolic supernatant was measured. Alternatively, in some experiments mitochondria were prepared with the Pierce isolation kit (64,65), and their protein content was determined. Aliquots of mitochondrial and cytosolic protein were analyzed by SDS-PAGE and immunoblotted with antibodies to cytochrome c (Santa Cruz Biotechnology, Santa Cruz, CA), tubulin, iPLA 2 ␤ (antibody 509 from Dr. Richard Gross, Washington University), and the mitochondrial marker cytochrome c oxidase complex IV-subunit II (Molecular Probes, Eugene, OR) (64).…”
Section: Methodsmentioning
confidence: 99%
“…Numbers under the blots represent VDAC-normalized changes in mitochondrial Elk-1 phosphorylation from four independent experiments. neurons exposed to DNA damage (Barrett et al, 2006) led us to investigate whether A␤ induces Elk-1 association with mitochondria and causes mitochondrial dysfunction. We found that A␤ increases the level of Elk-1 at mitochondria isolated from dissociated hippocampal neurons (Fig.…”
Section: Elk-1 Association With Mitochondria Is Involved In A␤-mediatmentioning
confidence: 99%
“…Extranuclear Elk-1 associates with mPTP in apoptotic neurons (Barrett et al, 2006) and has been implicated in neurodegenerative diseases including AD (Sharma et al, 2010). Because both CentA1 and Elk-1 can associate with mPTP and regulate its function (Barrett et al, 2006;Galvita et al, 2009) In this study, we show that the CentA1-Ras-Elk-1 pathway links A␤ and synaptic dysfunction. We found that A␤ upregulates CentA1 and activates the Ras-Elk-1 pathway at mitochondria, which impairs mitochondrial activity.…”
Section: Introductionmentioning
confidence: 99%